Formação humana na contemporaneidade: uma concepção segundo a subjetividade em Levinas - Carvalho, Cleusa Távora de (My University, 2025)
This dissertation is the result of theorical research of an exploratory nature which aimed to analyze aspects of Emmanuel Levinas' theory on subjectivity with a gaze to reviewing the concept of formation in contemporary times. The research was developed within the Intersubjectivity, language and education line of the Research Group on Education, philosophy and multiplicity in contemporary times. In this philosopher's conception, subjectivity is built on the primacy of the Other, in a break with modernity's metaphysics of consciousness, which affirms the primacy of the self and is justified intersubjectively. The motivation behind this work is to investigate the confluence between the Levinasian conception of subjectivity and welcoming with the contemporary debate on human formation. In this context, the proposed research problem was: Considering the limits identified in contemporary times on modern conceptions of humanism and formation, eminently based on a metaphysics of consciousness, what contributions from the Levinasian approach to subjectivity make it possible to revise and update the conception of human formation? With its development organized in three chapters, this dissertation presents subjectivity based on the descriptive analysis of sensitivity and language, in order to conceive it as intersubjectivity and, therefore, as a human encounter. This sensitivity is shown as acceptance and extends to the mode of dialogue. In turn, in the asymmetry of the relationship with the Other, the concepts of ethical teaching and teaching of the Other emerge. In conclusion, the significant contribution of this subjectivity to education can be cited as the reception of the Other as entirely Other, a reception that frees them from a reductionist and dominating process. And, by interposing education in contemporary times as the human phenomenon that is produced as an ethical event in the presence of a sensitive rationality mediated by language in the form of dialogue, mentions the ideas of subjectivity, according to Levinasian thought, which in evoking the human, become recognizably capable of composing a formative process in contemporary times. Finally, it adds that in a world dominated by rationalism, the encounter with another form of reason: the reason brought about by sensitivity, makes us less rational and more human by turning us towards the pre-existing sense of the sensible. [resumo fornecido pelo autor]
A presente dissertação resulta de pesquisa teórica de caráter exploratório e qualitativo que se propôs analisar aspectos da teoria de Emmanuel Levinas sobre a subjetividade com vistas a uma revisão do conceito de formação na contemporaneidade. A pesquisa foi desenvolvida junto à linha Intersubjetividade, linguagem e educação, do Grupo de pesquisa sobre Educação, filosofia e multiplicidade na contemporaneidade. Segundo Levinas, a subjetividade está construída no primado do Outro em ruptura com a metafísica da consciência da modernidade que afirma o primado do eu e está justificada intersubjetivamente. A motivação do trabalho está em investigar confluências entre a concepção levinasiana da subjetividade e do acolhimento com o debate contemporâneo sobre a formação humana. Neste contexto, o problema de pesquisa proposto foi: Considerando os limites identificados na contemporaneidade sobre as concepções modernas de humanismo e formação, eminentemente fundamentadas numa metafísica da consciência, quais contribuições da abordagem levinasiana sobre a subjetividade possibilitam revisar e atualizar a concepção de formação humana? Com seu desenvolvimento organizado em três capítulos, esta dissertação apresenta a subjetividade a partir da análise descritiva da sensibilidade e da linguagem, de modo a concebê-la como intersubjetividade e, portanto, como encontro humano. Sensibilidade essa que se mostra como acolhimento e que se estende ao modo do diálogo. Por sua vez, na assimetria da relação com o Outro, emergem os conceitos de docência ética e de docência do Outro. Já em um caráter conclusivo, pode ser citado como contribuição significativa dessa subjetividade à educação, o acolhimento do Outro como inteiramente Outro, uma recepção que o liberta de um processo reducionista e dominador. E, ao interpor a formação na contemporaneidade como fenômeno humano que se produz como acontecimento ético na presença de uma racionalidade sensível mediado pela linguagem ao modo do diálogo, menciona as ideias da subjetividade segundo o pensamento levinasiano, que na evocação do humano, se tornam reconhecidamente passíveis de compor um processo formativo na contemporaneidade. Por fim, acrescenta que em um mundo dominado pelo racionalismo, o encontro com uma outra forma de razão: a razão trazida pela sensibilidade, nos torna menos racionais e mais humanos ao nos voltar para o sentido pré-existente do sensível. [resumo fornecido pelo autor]
Keywords: Educação - Filosofia; Levinas, Emmanuel, 1906-1995; Ética; Subjetividade; Outro (Filosofia); Education - Philosophy; Ethics; Subjectivity; Other (Philosophy)